Immobilization of candida rugosa lipase onto n-vinyl-2-pyyrolidone-co-styrene for use in enantioselective esterification / Aiza Harun and Mahiran Basri - Harun, Aiza; Basri, Mahiran (2004)
Lipase from Candida rugosa was immobilized onto N-vinyl-2-pyyrolidone -co-styrene (VP-co-ST) hydrogel by an entrapment method. The percentage composition of monomer used to synthesizethe VP-co-ST hydrogel is (VP:ST)% ; 10:90 . The VP-co-ST hydrogel immobilized lipase was used to catalyze the enantioselective esterification of (R.S)-2-(4-chlorophenoxy) propanoic acid with n-tetradecanol to produce (R)- 2- (4 chlorophenoxy) propanoate and (S) - 2- (4-chJorophenoxy) propanoic acid. The VP-co-ST hydrogel immobilized lipase with the percentage of monomers 10:90 had beed chosen since it exhibited higher enantioselectivity compared with free lipase at optimum time 24 hours. The optimum temperature for the VP-co-ST hydrogel immobilized lipase and free lipase to catalyze the enantioselective esterification is at 40°C whereby the VP-co-ST hydrogel immobilized lipase exhibited higher enantioselectivity (enantiomeric excess) at 45%. The best solvent media for both lipases to catalyze the same reaction when using carbon tetrachloride, in which VP-co-ST hydrogel immobilized lipase showed higher percentage of enantioselectivity that is almost 50% compared to free lipase.